2018
DOI: 10.1007/s10633-018-9638-x
|View full text |Cite
|
Sign up to set email alerts
|

ISCEV extended protocol for the photopic negative response (PhNR) of the full-field electroretinogram

Abstract: The International Society for Clinical Electrophysiology of Vision (ISCEV) Standard for full-field electroretinography (ERG) describes a minimum procedure, but encourages more extensive testing. This ISCEV extended protocol describes an extension to the ERG Standard, namely the photopic negative response (PhNR) of the light-adapted flash ERG, as a well-established technique that is broadly accepted by experts in the field. The PhNR is a slow negative-going wave after the b-wave that provides information about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
105
0
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(119 citation statements)
references
References 22 publications
0
105
0
14
Order By: Relevance
“…The PhNR is a widely used protocol for assessing RGC and inner retinal function, 15 and was recently covered by ISCEV standards. 44 This study suggests that a loss in PhNR amplitude would depend on both the size and the location of the lesion, with peripheral lesions having a relatively greater impact than more central ones. This may explain the observation in other studies 9,10,45 that the full-field ERG is less sensitive to central lesions than peripheral ones.…”
Section: Discussionmentioning
confidence: 73%
“…The PhNR is a widely used protocol for assessing RGC and inner retinal function, 15 and was recently covered by ISCEV standards. 44 This study suggests that a loss in PhNR amplitude would depend on both the size and the location of the lesion, with peripheral lesions having a relatively greater impact than more central ones. This may explain the observation in other studies 9,10,45 that the full-field ERG is less sensitive to central lesions than peripheral ones.…”
Section: Discussionmentioning
confidence: 73%
“…10 It can be decreased in diseases that influence the inner retina, including glaucoma and different types of optic neuropathy. 11 Previous studies have reported a correlation between the amplitudes and latency of the PhNR with the mean RNFL thickness. This indicates that the RGC function is correlated to RNFL thickness.…”
Section: Introductionmentioning
confidence: 95%
“…The PhNR amplitude was identified as the difference between the baseline and the trough of the negative wave following the b-wave (Figure 1). 11 The implicit time was identified as the time interval from onset of the stimulus and the peak of the negative wave.…”
Section: Ophthalmological Examinationmentioning
confidence: 99%
“…The photopic negative (PhNR) and positive scotopic threshold responses are parameters of the electroretinogram (ERG) that are largely generated by RGCs in the inner retina. [26][27][28][29][30] RGC function has been shown to recover after acute and chronic IOP insults even after prolonged periods of functional loss. [31][32][33][34][35] Capacity for recovery is reduced with advancing age 36 and can be modified by interventions such as exercise and diet restriction.…”
Section: Main Textmentioning
confidence: 99%